Huli huli yan! - Wenceslao, Jose
Two responsible men trying to perfect their own craft, Olympio 'Ompong' Rocha (Dolphy) is a good provider and a very thoughtful big brother to his sister Marilou, while Sergeant Minor (Panchito) is a protective father, a single parent to his two grown-up children Raul & Lenny.